A STUDY ON THE CONNECTION BETWEEN LOSS AND SOLITUDE IN THE KOREAN WEBTOON KUBERA BY CURRYGOM - Sasidhar, Arunjith; Chellirian , B Sonia (International Journal of Psychosocial Rehabilitation, 2020)
Loss can be defined as the fact or process of losing something or someone and solitude can be defined as the state or situation of being alone. These two themes are intertwined and connected in the Korean Webtoon Kubera. The loss of people close to you like friends and family gives rise to trauma, loneliness and isolation in the story, but not everyone is uniformly affected or in the same way. How they try to cope with loss and solitude and the methods they use to alleviate their trauma, pain and suffering differs. This paper seeks to examine how loss and solitude are interconnected in Kubera and to what extent and how the different characters are affected.